Found in translation: the influence of the L1 on the reading of idioms in a L2 - Carrol, Gareth; Conklin, Kathy; Gyllstad, Henrik (Cambridge University Press, 2016)
Formulaic language represents a challenge to even the most proficient of language learners. Evidence is mixed as to whether native and nonnative speakers process it in a fundamentally dif- ferent way, whether exposure can lead to more nativelike processing for nonnatives, and how L1 knowledge is used to aid comprehension. In this study we investigated how advanced nonnative speakers process idioms encountered in their L2. We used eye-tracking to see whether a highly proficient group of L1 Swedes showed any evidence of a formulaic processing advantage for English idioms. We also compared translations of Swedish idioms and congruent idioms (items that exist in both languages) to see how L1 knowledge is utilized during online processing. Results support the view that L1 knowledge is automatically used from the earliest stages of processing, regardless of whether sequences are congruent, and that exposure and advanced proficiency can lead to nativelike formulaic processing in the L2.